2016
DOI: 10.1186/s13052-016-0300-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and its impact on asthma severity in asthmatic children

Abstract: BackgroundDespite obtaining evidences on association between vitamin D and development of lung in fetus, little is known about vitamin D level and its impact on severity of asthma in children. The present study aimed to assess the relationship between the asthma severity and vitamin D deficiency in asthmatic children.MethodsThis case-control study was conducted on 106 individuals including asthmatic (n = 53) and healthy children (n = 53) who referred to Mofid hospital in Tehran in 2013. The level of serum vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
1
21
0
6
Order By: Relevance
“…Low serum levels of 25(OH)D 3 or calcidiol have recently been associated with a decreased risk of asthma in childhood but an increased risk for eczema, 187 whereas most epidemiologic surveys and studies highlight a different landscape on this great concern. [188][189][190] The possibility, therefore, of ascertaining vitamin D's actual part in chronic allergy seems to be hampered by the complex role exerted by this hormonal molecule in innate immunity. [191][192][193][194] Particularly controversial is the role of vitamin D in atopic dermatitis.…”
Section: Role In Acquired and Regulatory Immunitymentioning
confidence: 99%
“…Low serum levels of 25(OH)D 3 or calcidiol have recently been associated with a decreased risk of asthma in childhood but an increased risk for eczema, 187 whereas most epidemiologic surveys and studies highlight a different landscape on this great concern. [188][189][190] The possibility, therefore, of ascertaining vitamin D's actual part in chronic allergy seems to be hampered by the complex role exerted by this hormonal molecule in innate immunity. [191][192][193][194] Particularly controversial is the role of vitamin D in atopic dermatitis.…”
Section: Role In Acquired and Regulatory Immunitymentioning
confidence: 99%
“…Among risk factors, Montella et al [ 2 ] reported that severe asthma was also associated with food sensitization but not with environmental exposure, comorbidities, medication adherence, exhaled nitric oxide levels, blood eosinophils and serum IgE levels. Asthmatics with vitamin D deficiency have been found to be not at risk for severe asthma [ 7 ]. However, the presence of asthma was strongly associated with low vitamin D levels in serum [ 7 , 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Asthmatics with vitamin D deficiency have been found to be not at risk for severe asthma [ 7 ]. However, the presence of asthma was strongly associated with low vitamin D levels in serum [ 7 , 8 ]. Treatment of asthma with vitamin D in schoolchildren was the aim of a randomized, double-blind, placebo-controlled trial [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…7 Though many studies have favored the notion that vitamin D deficiency increases the risk of recurrent wheezing and eventually development of asthma in pediatric age group there are other studies which have failed to demonstrate the beneficial effect of vitamin D supplementation on prevention of childhood asthma. 8 Similarly, the issue of antenatal vitamin D supplementation to pregnancy women for preventing development of asthma in children is the topic of intense debate amongst researchers and no unanimous guidelines exist in this regard. 9 In pediatric age group vitamin D status of the patients can be determined by estimation of 25 hydroxycholecalciferol.…”
Section: Discussionmentioning
confidence: 99%